2021
DOI: 10.1177/09673911211035068
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological characterization of sulfated chitosan oligomer as heparin mimics

Abstract: In the present study, chitosan oligomer was modified to sulfated chitosan oligomer (ShCsO) to mimic heparin. Its chemical structure was determined by infrared spectroscopy (FT-IR), X-ray diffractometry (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis. The results showed that the FT-IR spectrum band at 799 cm−1 corresponds to C–O–S and that at 1212 cm−1 corresponds to S=O bond stretching, which prove that the sulfate groups are incorporated into chitosan oligomer successfully. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Chitosan oligomers have two reflections at 2θ = 14°, 2θ = 24°. The reflection at 2 = 14° was associated with crystal form I (Kocabay et al, 2021). The XRD pattern of chitosan stearic acid shows two sharp diffraction peaks at 21.3 ° and 23.6 ° (Hamza et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan oligomers have two reflections at 2θ = 14°, 2θ = 24°. The reflection at 2 = 14° was associated with crystal form I (Kocabay et al, 2021). The XRD pattern of chitosan stearic acid shows two sharp diffraction peaks at 21.3 ° and 23.6 ° (Hamza et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Samet et al (85), it was found that sulfated chitosan oligomer (ShCsO) is a heparin mimetic. The researchers modified chitosan oligomers into ShCsO and studied its chemical composition and biological properties.…”
Section: Chitosan 6-o Sulfatementioning
confidence: 99%
“…Recently, researchers have greatly focused on the bioactivities of polysaccharides and their derivatives, especially sulfated polysaccharides (SPS) . SPS are anionic polymers consisting of several functional groups and possess a wide range of biological properties, such as antioxidant, anticoagulant, and antithrombic activities .…”
Section: Introductionmentioning
confidence: 99%